A 30-Day Adjunct Wellness Intervention for the Management of Extra-Articular Symptoms of Rheumatoid Arthritis: A Formative Study - Tara Hutson MSN, APRN, FNP-BC; Nicole Murman BA, RN; Donna Rolin PhD, APRN, PMHCNS-BC; Rakesh Jain MD, MPH; Andrew J. Laster MD, FACR; Steven P. Cole PhD; Saundra Jain MA, PsyD, LPC (SAGE Publishing, 2022)
Individuals with rheumatoid arthritis (RA) continually fall short of treatment targets using standard drug therapies alone. There is growing evidence that emphasizing physical and mental wellness is equally crucial for improving functioning among people with RA. The purpose of this formative study is to examine the feasibility of offering the wellness-based intervention ("KickStart30") in patients with RA. Thirteen individuals with RA on targeted immune modulators (a biologic or JAK inhibitor) enrolled in the KickStart30 program. Participants completed self-report measures of RA-specific disability (eg, pain) and other functional areas (eg, mood) in a pre- versus post- intervention design. Paired samples t- tests (and Related-Samples Wilcoxon Signed Rank Tests for non-normal distributions) detected statistically significant results for 10 of 12 measures, including reductions in pain ( M  = 4.54 to M  = 3.54; p   =   .025; BPI ), functional disability ( M  = 0.94 to M   =  0.73, p  = .032 ; HAQ-II ), cognitive and physical dysfunction ( M  = 25.46 to M = 13.54, p  < .001; CPFQ ), depressive symptoms ( M   =  9.31 to M   =  5.54, p  = .003; PHQ-9 ), anxiety ( M = 5.69 to M  = 3.23, p  = .005; GAD-7 ), insomnia ( M  = 11.62 to M   =  17.32, p   =  .007; Note: higher scores on the SCI indicate less insomnia), stress-related eating ( M  = 75.46 to M  = 84.54, p  = .021; Note: higher scores on the EADES indicate less stress-related eating), along with significant increases in mindfulness ( M  = 62.54 to M  = 67.85, p  = .040; MAAS ), mental wellness ( M = 4.46 to M  = 5.69; HERO ), and well-being ( M d  = 8.00 to M d  = 5.00, p  = .004; WHO-5 ). All significant measures had medium to large effect sizes (Cohen's d ). The study gives preliminary support for the possibility that the adjunct intervention may have an effect.